2007
DOI: 10.1080/08977190701781222
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin is a stress-response factor in fibroblasts subjected to hypoxia and acidosis

Abstract: The growth factor progranulin (granulin-epithelin precursor, PC-derived growth factor or acrogranin) regulates proliferation and migration and is implicated in cancer, development, wound repair and neurodegenerative diseases. Under most conditions fibroblasts do not express progranulin in vivo, however its expression is activated following wounding. We hypothesised that progranulin is part of a fibroblast stress response. Fibroblasts in culture were exposed to two physiologically and clinically relevant microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 37 publications
3
44
0
4
Order By: Relevance
“…In other cell types, PGRN is a potent extracellular antiapoptotic factor (16,21,74) and if this is true also for neurons, the loss of half the normal level of PGRN may sensitize the affected neurons to a range of traumatic shocks. Similarly, PGRN has roles in peripheral inflammation.…”
Section: Progranulin and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cell types, PGRN is a potent extracellular antiapoptotic factor (16,21,74) and if this is true also for neurons, the loss of half the normal level of PGRN may sensitize the affected neurons to a range of traumatic shocks. Similarly, PGRN has roles in peripheral inflammation.…”
Section: Progranulin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Of equal importance to the problems that accrue when PGRN levels are low is what happens to cells with increased exposure to PGRN. Elevated PGRN stimulates proliferation, (8)(9)(10)15,16,28,40) survival, (9,21,74) and motility (9,24,28) of epithelia, fibroblasts, and endothelia. PGRN activates typical growth factor signal transduction pathways such as the phosphorylation of shc and p44/42 mitogen-activated protein kinase (p44/42MAPK) in the extracellular regulated kinase (ERK) pathway as well as phosphatidylinositol 3-kinase (PI3K), protein kinase B/AKT, and the p70 S6 kinase in the PI3K pathway.…”
Section: Progranulin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Additionally, we characterized the expression of progranulin protein and mRNA in cirrhotic and non-cirrhotic livers. Progranulin is a growth factor involved in tumorigenesis, wound repair, neovascularization, inflammation, cell migration and mitosis (7), and cell survival (8). Progranulin expression was high in a mouse model of early diet-induced non-alcoholic steatohepatitis (9), and was recently identified in cultured primary and immortalized hepatic stellate cells (10), but it is not expressed in normal hepatocytes (11).…”
Section: Introductionmentioning
confidence: 99%
“…When applied to a cutaneous wound, progranulin increased the accumulation of neutrophils, macrophages, blood vessels, and fibroblasts in the wound (13), suggesting that progranulin could function as a chemotactic protein for myeloid-origin cell types and an angiogenic factor. A recent study showed that progranulin is an inducible protein in response to hypoxia or acidosis (14). Taken together, progranulin is an important molecule in inflammatory response and could therefore be involved in chronic subclinical inflammation associated with human obesity and type 2 diabetes.…”
mentioning
confidence: 99%